2020
DOI: 10.1186/s13014-020-01580-w
|View full text |Cite
|
Sign up to set email alerts
|

Novel role of PAF1 in attenuating radiosensitivity in cervical cancer by inhibiting IER5 transcription

Abstract: Background: Radiosensitivity is limited in cervical cancer (CC) patients due to acquired radiation resistance. In our previous studies, we found that immediate-early response 5 (IER5) is upregulated in CC cells upon radiation exposure and decreases cell survival by promoting apoptosis. The details on the transcriptional regulation of radiation-induced IER5 expression are unknown. Studies in recent years have suggested that Pol II-associated factor 1 (PAF1) is a pivotal transcription factor for certain genes "i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…A previous study showed that Pol II-associated factor 1 was upregulated in human cervical tumors and reduced the radiosensitivity of cervical cancer cells by inhibiting the transcription of immediate-early response 5. 26 Forkhead box protein M1 (FOXM1) and kinesin family member 20A (KIF20A) were highly expressed in irradiated human lung cancer cell lines and FOXM1 reduced the radiosensitivity of lung cancer cells partially by upregulating KIF20A. 27 These findings show the promise of protein regulators as therapeutic targets in the radiotherapies for human cancers.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A previous study showed that Pol II-associated factor 1 was upregulated in human cervical tumors and reduced the radiosensitivity of cervical cancer cells by inhibiting the transcription of immediate-early response 5. 26 Forkhead box protein M1 (FOXM1) and kinesin family member 20A (KIF20A) were highly expressed in irradiated human lung cancer cell lines and FOXM1 reduced the radiosensitivity of lung cancer cells partially by upregulating KIF20A. 27 These findings show the promise of protein regulators as therapeutic targets in the radiotherapies for human cancers.…”
Section: Discussionmentioning
confidence: 97%
“…FOXC2 and ADAM12 were both upregulated in response to radiation, and knockdown of FOXC2 inhibited the proliferative ability of irradiated HNSCC cells. A previous study showed that Pol II‐associated factor 1 was upregulated in human cervical tumors and reduced the radiosensitivity of cervical cancer cells by inhibiting the transcription of immediate‐early response 5 26 . Forkhead box protein M1 (FOXM1) and kinesin family member 20A (KIF20A) were highly expressed in irradiated human lung cancer cell lines and FOXM1 reduced the radiosensitivity of lung cancer cells partially by upregulating KIF20A 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The function of PAF1C in hindering pause release was initially found by forward genetic screens in zebrafish, showing that PAF1C antagonizes the release of erythroid genes (32). This was later confirmed by reverse genetic screens in human cells using highly paused genes as readouts (12) and supported by studies demonstrating inhibitory roles of PAF1C in transcription especially pausing in varying contexts (21,22,28,(39)(40)(41)(42)(43). However, the role of PAF1C in promoting pause release has also been reported in several studies under different biological settings (17,22,23,44).…”
Section: Introductionmentioning
confidence: 84%
“…In S. pombe, previous studies have found that high dNTP levels can lead to increased DNA damage sensitivity and slow progression through S-phase (Fleck et al, 2013;Pai and Kearsey, 2017). A recent study has suggested a role for PAF1 in attenuating radiosensitivity by inhibiting immediate-early response 5 (IER5) transcription, which is involved in cell cycle regulation (Ding et al, 2019;Zheng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%